(untitled) (Scientific journal of the Fergana State University, 2023)
The article notes that the results of stratigraphic excavations carried out by VM Masson at the Yazdepa monument to substantiate the chronology of the Early Iron Age do not cover all of Central Asia to date, and the Yaz-II archeological complex may belong only to the southern Amu Darya.